2013
DOI: 10.5935/abc.20130214
|View full text |Cite
|
Sign up to set email alerts
|

P Wave Indices to Predict Atrial Fibrillation Recurrences Post Pulmonary Vein Isolation

Abstract: BackgroundP-wave indices are appealing markers for predicting atrial fibrillation (AF) recurrences post ablation.ObjectiveThis study evaluates the value of P wave indices to predict recurrences post pulmonary vein isolation (PVI) in patients with paroxysmal AF.MethodsWe selected 198 patients (57 ± 8 years, 150 males) with symptomatic drug-refractory paroxysmal AF undergoing PVI in our hospital. A 12-lead electrocardiogram was used to measure P wave duration in lead II, P wave terminal force (PWTF) in lead V1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…We included twelve studies for qualitative synthesis, and twelve studies were available for meta‐analysis. There were 1,482 patients with AF post‐PVI from twelve cohort studies (Blanche, Tran, Rigamonti, Burri, & Zimmermann, ; Caldwell et al, ; Hagiwara et al, ; Weber et al, ; Knecht et al, ; Masuda et al, ; Mugnai et al, ; Nakatani et al, ; Ogawa et al, ; Okumura et al, ; Salah et al, ; Wu et al, ; Table ). The subjects had either persistent or paroxysmal AF, and standard 12‐lead ECG measured the PWD in seven studies and signal‐averaged ECG in four studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We included twelve studies for qualitative synthesis, and twelve studies were available for meta‐analysis. There were 1,482 patients with AF post‐PVI from twelve cohort studies (Blanche, Tran, Rigamonti, Burri, & Zimmermann, ; Caldwell et al, ; Hagiwara et al, ; Weber et al, ; Knecht et al, ; Masuda et al, ; Mugnai et al, ; Nakatani et al, ; Ogawa et al, ; Okumura et al, ; Salah et al, ; Wu et al, ; Table ). The subjects had either persistent or paroxysmal AF, and standard 12‐lead ECG measured the PWD in seven studies and signal‐averaged ECG in four studies.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies reported a statistically significant difference between the mean PWD of subjects with recurrent AF and those without (Blanche et al, ; Caldwell et al, ; Hagiwara et al, ; Mugnai et al, ; Nakatani et al, ; Ogawa et al, ; Okumura et al, ; Salah et al, ; Wu et al, ). Pooled mean difference of P‐wave duration in subjects with recurrent AF and non‐recurring AF was 12.54 ms [8.76–16.31]; p < 0.001 and high heterogeneity I 2 78%, p < 0.001 (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some have been proposed, such as maximum (Pmax) 9 and minimum P-wave duration, 10 P-wave terminal force in lead V1 11 and P-wave dispersion (PWD). [12][13][14][15] Although AF has been associated with increased blood pressure (BP) and UA levels, there are still no studies worldwide that address the relation between Pmax plus PWD and BP plus UA in patients over 60 years of age, in whom there is an increased risk of AF. Taking these elements into account, our study aimed to characterize Pmax and PWD according to BP and UA levels in geriatric patients in a health clinic.…”
mentioning
confidence: 99%